Experiential learning using Google Classroom on students’ academic performance and motivation in language subject - Ping, Loh Boon; Mohd Zaid, Norasykin; Ibrahim, Nor Hasniza; Surif, Johari; Megat Zakaria, Megat Aman Zahiri; Permadi, Hendro (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigates the effectiveness of experiential learning using Google Classroom on year 2 students’ academic performance and motivation in Malay language. This study also highlighted the elements in Google Classroom’s experiential learning that motivate students to achieve academic performance. The study conducted with 32 students at Chinese primary school in Johor Bahru; utilized online pre-tests, post-tests, and 5-point Likert scale online questionnaire to identify students’ motivation level. Results revealed significant improvements in students’ Malay language post-test scores, indicating the effectiveness of experiential learning using Google Classroom. Descriptive statistics showed a high level of student motivation, significantly motivated by the experiential learning treatment using Google Classroom, with the materials provided by the teacher being the most preferred by students and effective element in motivating them to achieve academic success. The study suggests that implementing experiential learning with Google Classroom positively influences academic performance in Malay language. Teachers, schools, and communities are suggested to review current learning methods and platforms; and strive to incorporate experiential learning through Google Classroom to enhance students’ academic performance in Malay language. Future studies are encouraged to provide more reliable data, particularly within the context of Chinese primary schools in Malaysia, to further enrich educational practices.